Philosophical and Modern Scientific Revival of John Duns Scotus in Defense of Principle of Causality - Roshlan Rahman Dipto; Md. Iftakhar Hossain Simanto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
In this paper, the causal principle,